If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 26.4 Reorder the terms: 2(-1 + x) = 26.4 (-1 * 2 + x * 2) = 26.4 (-2 + 2x) = 26.4 Solving -2 + 2x = 26.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 26.4 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 26.4 + 2 2x = 26.4 + 2 Combine like terms: 26.4 + 2 = 28.4 2x = 28.4 Divide each side by '2'. x = 14.2 Simplifying x = 14.2
| a^2+a-3a-3=0 | | ln(2x)=7 | | 2t^2-12t-25=0 | | -6+x=.6x-2.2+2 | | X+4=9+2x | | 35x-23=17 | | y=-5x+10 | | 0=6x+x^2+9 | | 7x-28=21 | | y=x+50 | | 3x+5=9x-(5-2x) | | x-(3x+1)=2x-(4x+3)-x | | 7p+12=13+6p | | 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= | | 2m(11n)= | | 2m(11n+3)= | | 0.4x+5.2=4.6 | | 9(2x-4)=3(6x+1) | | x^2-11x-7=0 | | 4t+3=2t+11 | | 4-9x=-11x | | 3-(x-1)=x+2 | | 12-3x=8x+2 | | 4+8x+25-5y=23 | | 103-7x=11x+23 |